Semiotic Analysis of Dove’s Femvertising - Chun Hojeung; Setefanus Suprajitno (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
This qualitative study aimed to know in what ways the verbal (oral mode) and non-verbal (visual mode and gestural mode) semiotic resources help Dove meet the criteria of femvertising. The study used the Multimodal approach to help analyze the data. The writer collected and analyzed the data from Dove’s My Beauty My Say video. The findings showed that the verbal semiotic resources help Dove meet the criteria of femvertising by orally informing the audiences about the problems and arguments that are faced by the women in the video and how they responded to the problems in order to empower all the women. Meanwhile, the non-verbal semiotic resources help Dove meet the criteria of femvertising by revealing women in the authentic form and outside of traditional gender stereotypes so that they can deliver predominantly pro-female messages that can empower themselves and other women who are facing the similar problems as they do. The non-verbal semiotic resources are delivered by using the gestures (e.g. facial expression and body language) and objects (e.g. outfits, dominated background color, focus of the camera) in the video. In conclusion, I observe these semiotic resources are important to help Dove meet the criteria of femvertising.  Keywords: Femvertising, Multimodal, Verbal semiotic resources, Non-verbal semiotic resources